Republic of Kazakhstan : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This paper analyzes the Republic of Kazakhstan's 2013 Article of Consultation. The IMF report focuses on vision of developing Kazakhstan into a leading emerging market economy requires concerted efforts to strengthen the policy architecture. It highlights the importance of enhancing the diversification strategy by strengthening institutions, the business environment, and human capital, while carefully managing the country's oil wealth. It also discusses that the unification of the pension funds has become a policy priority. The medium-term growth prospects appear to be strong, driven by a substantial projected increase in oil output.